Paghilom a special project presentation on grief, music and healing - Dolorosa, Via Loris C.; Timbol-Guadalupe, Jocelyn (Diliman, Quezon City U.P. College of Music, 2019)
The project aims to create a music therapy intervention plan for families who lost a loved one. The intervention plan covers the minimum period of five months, which includes the process of planning, assessment, and the intervention itself. The music intervention plan consists of various musical activities comprising of: listening, improvisation, composition and songwriting, singing and playing. Meditation and art activities will be added as well to provide the expression of unprocessed emotions, and also to soothe and relax the mind of the participants.
Thesis (B. M. Music Education) -- University of the Philippines, Diliman.
Keywords: Music therapy